Development of Multimodal Stimulator for Studying Human Tactile Perception and Cognitive Functions: Preliminary Results - Soon-Cheol Chung; Jinsu An; Kyu-Beom Kim; Mi-Hyun Choi; Hyung-Sik Kim (Applied Sciences)
Humans mostly perceive tactile sensations in daily life as a combination of warmth, vibration, and pressure. To understand the complex tactile perception and cognitive processes, in this study, we aimed to develop a multimodal stimulator and investigate changes in neuronal activity. An actuator that can display warmth (W), vibration (V), and pressure (P) on the distal region of the index finger has been developed. Preliminary experiments were conducted with nine subjects. Electroencephalograms were measured for six tactile stimuli—three single stimuli (W, V, and P) and three combination stimuli (W + V, V + P, and W + V + P)—and event-related desynchronization/synchronization (ERD/S) analysis were performed. The actuator can present all kinds of stimuli in the same location and control stimulation parameters quantitatively. For all experiments, there was an ERD in the α and β bands about 0.5 s after stimulation followed by ERS was observed in the C3 area. The change in the peak-to-peak value was the largest for warmth and the smallest for pressure. In contrast, in the duration of the ERD, W was the shortest and P was the longest. As stimulus presented simultaneously, the ERD became longer in both the alpha and beta bands. In the beta band, the peak of ERD became larger. The developed system was confirmed to be capable of providing valid tactile stimulation, inducing appropriate neuronal activation, and enabling multimodal tactile research.